A morphosyntactic analysis of nominal expressive suffixes in Russian and Greek - Olga Steriopolo; Giorgos Markopoulos; Vassilios Spyropoulos (The Linguistic Review, 2021)
This work investigates and compares nominal expressive suffixes in Russian and Greek within the framework of Distributed Morphology. It shows that, although the suffixes under investigation share the same expressive meaning, they differ significantly in their syntactic structure, namely in the manner and place of attachment in the syntactic tree. More specifically, in both languages expressive suffixes can attach either as heads or as modifiers and, furthermore, they may occupy various syntactic positions. This illustrates that, despite their uniformity at semantic level, expressive suffixes exhibit variation with respect to their syntactic structuring both within and across languages.